The The Effect of Gamma Irradiation on In Vitro Explant Growth, Shoot Multiplication, and Plantlet Regeneration Explants Bulbil of Porang (Amorphophallus muelleri Blume) - Ni'amul Albab, Muhammad; Widoretno, Wahyu; Siswanto, Dian; Waluyo, Budi; Mertasari, Chaerani (Graduate School, Universitas Brawijaya, 2025)
Porang (Amorphophallus muelleri Blume) is a tuberous plant that contains glucomannan as an alternative in reducing obesity. It is widely traded, but it is cultivated through conventional methods and takes a long time. In vitro mutagenesis technique with gamma irradiation is expected to increase the production of superior porang. This study aims to determine the effect of gamma irradiation on explant growth, shoot multiplication, and plantlet regeneration on in vitro culture. The doses of gamma irradiation, i.e. 0, 2, 4, 6, 8, and 10 gamma rays (Gy). Explants bulbil were precultured for 14 days on Murashige and Skoog (MS) medium fortified with 6-benzyl amino purine (BAP) 3 mg.L-1 before irradiation. The irradiated explants were then cultured on media containing MS supplemented with α-naphthalene acetic acid (NAA) 0.1 mg.L-1 and BAP 3 mg.L-1 for 4 and 8 weeks of culture. Plantlet regeneration media was MS supplemented with NAA 0.1 mg.L-1 for 4 weeks of culture. The results showed that a dose of 10 Gy gamma irradiation was able to inhibit explant growth (0.06 g), shoot multiplication (0%), and plantlet height (0.38 cm), while gamma irradiation at a dose of 6 Gy increased explant growth (0.16 g), shoot multiplication (40%), and plantlet height (5.60 cm). The lethal dose 50 (LD50) of gamma irradiation for explant survival rate is 8.79 Gy. Keywords: Amorphophallus muelleri, explant growth, gamma irradiation, in vitro, plantlet regeneration, shoot multiplication